Satire and Realism in Jane Austen’s Pride and Prejudice: an Interpretative Analysis - Aziz Ahmad (University of Chitral Journal of Linguistics and Literature)
Jane Austen is acknowledged for the application of realism and satire in her novels. This paper focuses on the analysis of realism and satire in Jane Austen’s Pride and Prejudice; however, her entire oeuvre spotlights the features (of satire and realism) alongside robust feminism: typical of her literary taste and temperament, not necessarily of the Romantic Age which she lived in. Rigorous analysis and realistic observation reveals that the employment of realism and satire in Pride and Prejudice, are quite obvious, in all sorts of aspects including narrative, settings, themes and characters. Analysis of the novel under study leads to the observation that satire and realism go hand in hand in the said novel—intermittently—and thoughtfully. Conclusively, it is observed that Jane Austen’s literary life had a tremendous influence on how to subsume realism (primarily through matrimonies) of age and satire on a romantic society (whereby ideals collapse headlong), in Pride and Prejudice.